Ultralow-sheet-resistance ITO film with better chromatic aberration and preparation method of ultralow-sheet-resistance ITO film
By using indium tin target plating and fractional plating technology with different parameter ratios in the ITO film, combined with aging and crystallization, the problem of large chromatic difference changes before and after etching of the ITO film is solved, and ultra-low square resistance ITO with better color difference is achieved Film, meets high requirements for transparency and conductivity.
Patent Information
- Application Number
- CN202411352537.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
During the etching process, the existing ITO films are prone to undergo large changes in color difference before and after etching, which affects its transparency and conductivity, and thus affects the use effect of the EC dimming film.
Two different indium tin mixed targets with different parameters and ratios are used to plating the ITO layer, and through the plating and aging crystallization technology, the thickness of the ITO layer and the molar ratio and thickness of the silicon-aluminum mixed layer are controlled, the coating stress is reduced, and the ITO layer is promoted. The layer is sufficiently crystallized, thereby reducing the color difference value before and after etching.
It effectively reduces the color difference value before and after etching of the ITO film, reaching ≤1%, meeting the high requirements of users, and ensuring the transparency and conductivity of the ITO film.
Smart Images

Figure CN119220931A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ITO films, and in particular relates to an ultra-low square resistance ITO film with better color difference and a preparation method thereof. Background Art
[0002] EC dimming film, or electrochromic dimming film, can undergo stable and reversible color changes under the action of an external electric field through the material's optical properties such as reflectivity, transmittance, and absorptivity, thereby appearing as a reversible change in color and transparency. EC dimming film is generally composed of multiple layers of thin films, including a transparent conductive layer, an electrochromic layer, an electrolyte layer, an ion storage layer, etc.
[0003] ITO film is indium tin oxide film. It is mainly used as a transparent electrode in EC dimming film. In the structure of electrochromic devices, ITO film not only allows light to pass through, but also provides a path for electron transmission to achieve color and transparency adjustment. ITO film needs to be etched in specific applications to form a specific electrode pattern in order to control the changes in the electrochromic layer under the action of an electric field. The existing ITO film will have a large color difference before and after etching during the etching process, which can easily reduce the transparency and conductivity of the ITO film, and thus affect the use effect of the EC dimming film.
[0004] Therefore, how to reduce the color difference before and after etching of the ITO film is a problem that needs to be solved at present.
[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0006] The purpose of the present invention is to provide an ultra-low square resistance ITO film with better color difference and a preparation method thereof. The ITO film of the present invention has low square resistance, excellent conductivity, and small color difference before and after etching, which can meet the high requirements of users.
[0007] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0008] An ultra-low square resistance ITO film with better color difference comprises a substrate layer, on which an upper coating layer, a primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially stacked;
[0009] The first ITO layer is formed by plating two indium tin mixed targets with different doping ratios, wherein the indium tin molar ratio of one indium tin mixed target is (80-99):(1-20) based on indium tin atoms, and the indium tin molar ratio of the other indium tin mixed target is (88-95):(5-12) based on indium tin atoms;
[0010] The second ITO layer is formed by plating two indium tin mixed targets with different doping ratios, wherein the molar ratio of indium tin in one indium tin mixed target is (80-99):(1-20) based on indium tin atoms, and the molar ratio of indium tin in the other indium tin mixed target is (88-95):(5-12) based on indium tin atoms.
[0011] In one or more embodiments of the present invention, the thickness of the first ITO layer is 50-250 nm.
[0012] In one or more embodiments of the present invention, the thickness of the second ITO layer is 50-150 nm.
[0013] In one or more embodiments of the present invention, the molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is (75-99): (1-25) based on silicon and aluminum atoms.
[0014] In one or more embodiments of the present invention, the thickness of the silicon-aluminum mixed layer is 1 to 30 nm.
[0015] In one or more embodiments of the present invention, the base material is selected from SiO 2 、Ti、TiO 2 、Si、Al 2 O 3 MgF 2 、SiO、HfO 2 SnO 2 and Y 2 O 3 .
[0016] In one or more embodiments of the present invention, the thickness of the primer layer is 0.2-20 nm.
[0017] In one or more embodiments of the present invention, a lower coating layer is provided on the side of the substrate layer facing away from the upper coating layer, and both the upper coating layer and the lower coating layer are acrylic resin layers.
[0018] Another specific embodiment of the present invention provides a technical solution as follows:
[0019] A method for preparing an ultra-low square resistance ITO film with better color difference comprises the following steps:
[0020] Taking a substrate layer, coating an upper coating layer and a lower coating layer on both sides of the substrate layer respectively, and setting a high temperature protective film on the lower coating layer;
[0021] A primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially plated on the upper coating layer;
[0022] A positive protective film is provided on the second ITO layer.
[0023] In one or more embodiments of the present invention, the vacuum degree during plating is 1×10 -4 Pa or less, the water vapor value is 9×10 -5 Below pa, the reaction gas is a mixed gas of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is (60-80):(20-35):(5-10).
[0024] Compared with the prior art, the present invention adopts two indium tin targets with different doping ratios to plate the ITO layer, which effectively reduces the color difference before and after etching of the ITO film, and the color difference before and after etching reaches ≤1%. The color difference of the existing ITO film before and after etching is relatively large, generally around 2%. Obviously, the ITO film in the present invention can better meet the high requirements of users. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 Schematic diagram of the structure of an ultra-low square resistance ITO film with better color difference in one embodiment of the present invention.
[0027] Description of main reference numerals:
[0028] 1. High temperature protective film; 2. Lower coating layer; 3. Substrate layer; 4. Upper coating layer; 5. Primer layer; 6. Silicon-aluminum mixed layer; 7. First ITO layer; 8. Second ITO layer; 9. Positive protective film. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0030] A specific embodiment of the present invention provides an ultra-low square resistance ITO film with better color difference, comprising a substrate layer, on which an upper coating layer, a primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially stacked;
[0031] The first ITO layer is formed by plating two indium tin mixed targets with different doping ratios, wherein the indium tin molar ratio of one indium tin mixed target is (80-99):(1-20) based on indium tin atoms, and the indium tin molar ratio of the other indium tin mixed target is (88-95):(5·12) based on indium tin atoms.
[0032] The second ITO layer is formed by plating two indium tin mixed targets with different doping ratios. The molar ratio of indium tin in one indium tin mixed target is (80·99): (1-20) based on indium tin atoms, and the molar ratio of indium tin in the other indium tin mixed target is (88·95): (5·12) based on indium tin atoms.
[0033] Specifically, the ITO layer needs to be aged and crystallized after plating. The purpose of aging and crystallization is not only to improve the conductivity and optical properties of the ITO layer, but also to ensure the effect of the subsequent etching process. If the ITO layer is not fully crystallized, the etching rate and uniformity may be reduced, which may easily lead to a large color difference between the ITO film before and after etching. The present invention first divides the ITO layer into two platings, which reduces the possibility that the stress of the plating layer cannot be effectively released when a thicker ITO layer is plated at one time, and promotes the full crystallization of the ITO layer during the aging and crystallization process. In addition, the present invention uses indium tin targets with different doping ratios to plate the ITO layer, which can further improve the crystallization degree and performance of the ITO layer. After etching, the color difference before and after etching of the ITO film meets ≤1%, which effectively reduces the color difference before and after etching of the ITO film.
[0034] In a specific embodiment, the thickness of the first ITO layer is 50·250 nm.
[0035] In a specific embodiment, the second ITO layer has a thickness of 50-150 nm.
[0036] Specifically, by controlling the thickness of the first ITO layer and the second ITO layer, the possibility of the coating stress not being effectively released is reduced, so that the ITO layer can be fully crystallized and obtain a better crystallization state, which is beneficial to reducing the color difference change of the ITO film during the etching process, thereby ensuring the transparency and conductivity of the ITO film.
[0037] In one specific embodiment, the molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is (75-99): (1-25) based on silicon and aluminum atoms.
[0038] In one specific embodiment, the thickness of the silicon-aluminum mixed layer is 1-30 nm.
[0039] Specifically, by limiting the thickness of the silicon-aluminum mixed layer and the silicon-aluminum molar ratio, the conductivity and optical properties of the ITO film can be improved and the color difference of the film layer can be reduced.
[0040] In one embodiment, the base material is selected from SiO2 、Ti、TiO 2 、Si、Al 2 O 3 MgF 2 、SiO、HfO 2 SnO 2 and Y 2 O 3 .
[0041] In one specific embodiment, the thickness of the primer layer is 0.2-20 nm.
[0042] Specifically, selecting the above types of primer layers and controlling the thickness of the primer layers can improve the adhesion of the film layer and increase the stability of the ITO film.
[0043] In a specific embodiment, a lower coating layer is provided on the side of the substrate layer facing away from the upper coating layer, and both the upper coating layer and the lower coating layer are acrylic resin layers.
[0044] Specifically, the thickness of the lower coating layer is 20 to 900 nm, and the thickness of the upper coating layer is 40 to 900 nm. The upper coating layer and the lower coating layer of a certain thickness are formed by coating with an acrylic resin coating liquid, which can improve the wear resistance and scratch resistance of the ITO film and optimize the optical properties of the ITO film.
[0045] In a specific embodiment, the substrate layer is a PET layer, a PI layer, a TAC layer, a COP layer or a PC layer, and the thickness of the substrate layer is 5.7 to 250 μm.
[0046] Another specific embodiment of the present invention provides a method for preparing an ultra-low square resistance ITO film with better color difference, comprising steps 1-3.
[0047] Step 1: Take a substrate layer, coat an upper coating layer and a lower coating layer on both sides of the substrate layer respectively, and set a high-temperature protective film on the lower coating layer.
[0048] Specifically, the upper coating layer and the lower coating layer are both acrylic resin layers, which are formed by coating with a conventional acrylic resin coating liquid. In the subsequent magnetron sputtering coating process, the high temperature protective film can protect the film surface appearance and coating stability. The high temperature protective film is a PET film with a thickness of 30 to 188 μm.
[0049] Step 2: sequentially plate a primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer on the upper coating layer.
[0050] Specifically, during plating, the vacuum degree is 1×10 -4 Pa or less, the water vapor value is 9×10 -5Below pa, the reaction gas is a mixture of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is (60-80): (20-35): (5-10). By controlling the vacuum degree, water vapor value and reaction gas, the accuracy and stability of the plating can be ensured, and a coating with better performance can be obtained.
[0051] Step 3, setting a positive protective film on the second ITO layer.
[0052] Specifically, the positive protective film is a PET film, which can protect the ITO film from being scratched.
[0053] The present invention is further described in detail below in conjunction with specific embodiments.
[0054] Example 1
[0055] The ultra-low square resistance ITO film with better color difference includes, from bottom to top, a stacked PET high-temperature protective film of 50μm, a lower coating layer of 20nm, a PI substrate layer of 38μm, an upper coating layer of 100nm, a base layer of 8nm, a silicon-aluminum mixed layer of 5nm, a first ITO layer of 50nm, a second ITO layer of 50nm, and a PET positive protective film of 40μm. Among them, the base layer is made of TiO 2 The molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is 75:25 based on silicon and aluminum atoms.
[0056] During the preparation, a PI film is taken, and a coating liquid of acrylic acid resin is coated on both sides of the PI film respectively, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high temperature protective film is attached to the lower coating layer.
[0057] Then dry magnetron vacuum sputtering was used to control the vacuum degree to 1×10 -4 Pa below, the water vapor value reaches 9×10 -5 Below pa, the reaction gas is a mixed gas of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is 70:20:10. A primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially plated on the upper coating layer. When plating the first ITO layer, two indium tin targets of equal number are selected for plating, and the indium tin molar ratio of one indium tin target is 80:20 based on indium tin atoms, and the indium tin molar ratio of the other indium tin target is 88:12 based on indium tin atoms. When plating the second ITO layer, two indium tin targets of equal number are selected for plating, and the indium tin molar ratio of one indium tin target is 80:20 based on indium tin atoms, and the indium tin molar ratio of the other indium tin target is 88:12 based on indium tin atoms.
[0058] After plating, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes, and then a PET positive protective film is attached to the second ITO layer to obtain an ultra-low square resistance ITO film with better color difference.
[0059] Example 2
[0060] The ultra-low square resistance ITO film with better color difference includes, from bottom to top, a stacked PET high-temperature protective film of 188μm, a lower coating layer of 150nm, a PI substrate layer of 80μm, an upper coating layer of 250nm, a base layer of 15nm, a silicon-aluminum mixed layer of 30nm, a first ITO layer of 250nm, a second ITO layer of 250nm, and a PET positive protective film of 40μm. Among them, the base layer is made of TiO 2 The molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is 99:1 based on silicon and aluminum atoms.
[0061] During the preparation, a PI film is taken, and a coating liquid of acrylic acid resin is coated on both sides of the PI film respectively, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high temperature protective film is attached to the lower coating layer.
[0062] Then dry magnetron vacuum sputtering was used to control the vacuum degree to 1×10 -4 Pa below, the water vapor value reaches 9×10 -5 Below pa, the reaction gas is a mixed gas of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is 70:20:10. A primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially plated on the upper coating layer. When plating the first ITO layer, two indium tin targets of equal number are selected for plating, and the indium tin molar ratio of one indium tin target is 85:15 based on indium tin atoms, and the indium tin molar ratio of the other indium tin target is 95:5 based on indium tin atoms. When plating the second ITO layer, two indium tin targets of equal number are selected for plating, and the indium tin molar ratio of one indium tin target is 85:15 based on indium tin atoms, and the indium tin molar ratio of the other indium tin target is 95:5 based on indium tin atoms.
[0063] After plating, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes, and then a PET positive protective film is attached to the second ITO layer to obtain an ultra-low square resistance ITO film with better color difference.
[0064] Example 3
[0065] The ultra-low square resistance ITO film with better color difference includes, from bottom to top, a stacked PET high temperature protective film of 100μm, a lower coating layer of 400nm, a PI substrate layer of 188μm, an upper coating layer of 400nm, a base layer of 20nm, a silicon-aluminum mixed layer of 20nm, a first ITO layer of 100nm, a second ITO layer of 100nm, and a PET positive protective film of 40μm. Among them, the base layer material is TiO 2 The molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is 85:15 based on silicon and aluminum atoms.
[0066] During the preparation, a PI film is taken, and a coating liquid of acrylic acid resin is coated on both sides of the PI film respectively, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high temperature protective film is attached to the lower coating layer.
[0067] Then dry magnetron vacuum sputtering was used to control the vacuum degree to 1×10 -4 Pa below, the water vapor value reaches 9×10 -5 pa or less, the reaction gas is a mixed gas of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is 70:20:10. A primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially plated on the upper coating layer. When the first ITO layer is plated, two indium tin targets of equal number are selected for plating, and the indium tin molar ratio of one indium tin target is 99:1 based on indium tin atoms, and the indium tin molar ratio of the other indium tin target is 90:10 based on indium tin atoms. When the second ITO layer is plated, two indium tin targets of equal number are selected for plating, and the indium tin molar ratio of one indium tin target is 99:1 based on indium tin atoms, and the indium tin molar ratio of the other indium tin target is 90:10 based on indium tin atoms.
[0068] After plating, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes, and then a PET positive protective film is attached to the second ITO layer to obtain an ultra-low square resistance ITO film with better color difference.
[0069] Comparative Example 1
[0070] The ultra-low square resistance ITO film with better color difference includes, from bottom to top, a stacked PET high-temperature protective film of 50μm, a lower coating layer of 20nm, a PI substrate layer of 38μm, an upper coating layer of 100nm, a base layer of 8nm, a silicon-aluminum mixed layer of 5nm, a first ITO layer of 50nm, a second ITO layer of 50nm, and a PET positive protective film of 40μm. Among them, the base layer is made of TiO 2 The molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is 75:25 based on silicon and aluminum atoms.
[0071] During the preparation, a PI film is taken, and a coating liquid of acrylic acid resin is coated on both sides of the PI film respectively, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high temperature protective film is attached to the lower coating layer.
[0072] Then dry magnetron vacuum sputtering was used to control the vacuum degree to 1×10 -4 Pa below, the water vapor value reaches 9×10 -5Below pa, the reaction gas is a mixed gas of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is 70:20:10. A primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially plated on the upper coating layer. When the first ITO layer is plated, the same indium tin target is selected for plating, and the molar ratio of indium tin in the indium tin target is 80:20 based on indium tin atoms. When the second ITO layer is plated, the same indium tin target is selected for plating, and the molar ratio of indium tin in the indium tin target is 80:20 based on indium tin atoms.
[0073] After plating, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes, and then a PET positive protective film is attached to the second ITO layer to obtain an ultra-low square resistance ITO film with better color difference.
[0074] Comparative Example 2
[0075] The ultra-low square resistance ITO film with better color difference includes, from bottom to top, a stacked PET high-temperature protective film of 50μm, a lower coating layer of 20nm, a PI substrate layer of 38μm, an upper coating layer of 100nm, a base layer of 8nm, a silicon-aluminum mixed layer of 5nm, a first ITO layer of 50nm, a second ITO layer of 50nm, and a PET positive protective film of 40μm. Among them, the base layer is made of TiO 2 The molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is 75:25 based on silicon and aluminum atoms.
[0076] During the preparation, a PI film is taken, and a coating liquid of acrylic acid resin is coated on both sides of the PI film respectively, and after drying, an upper coating layer and a lower coating layer are formed, and a PET high temperature protective film is attached to the lower coating layer.
[0077] Then dry magnetron vacuum sputtering was used to control the vacuum degree to 1×10 -4 Pa below, the water vapor value reaches 9×10 -5 Below pa, the reaction gas is a mixed gas of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is 70:20:10. A primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially plated on the upper coating layer. When plating the first ITO layer, the same indium tin target is selected for plating, and the molar ratio of indium tin in the indium tin target is 99:1 based on indium tin atoms. When plating the second ITO layer, the same indium tin target is selected for plating, and the molar ratio of indium tin in the indium tin target is 99:1 based on indium tin atoms.
[0078] After plating, the film material is placed in an oven at 150°C for aging and crystallization for 5 minutes, and then a PET positive protective film is attached to the second ITO layer to obtain an ultra-low square resistance ITO film with better color difference.
[0079] The following performance tests were performed on the ITO films in each embodiment and each comparative example:
[0080] (1) After the plating is completed and the machine is removed, 10 points are taken on average according to the film width and the square resistance of the 10 points is tested before and after aging and crystallization. The film width is 1200mm. During the test, the film material is placed flat on the table with the film surface facing up. The surface square resistance is tested with a square resistance meter. After aging and crystallization, the resistance value is required to reach 8±2Ω. The results are shown in Table 1.
[0081] (2) After the coating is completed and the machine is removed, three samples are cut according to the average film width, with a sample size of 340*340mm. The samples are baked in a 150℃ oven for 5 minutes. After the baking is completed, wait until the temperature drops below 70℃, take out the samples, place the sample film surface facing up on the table, and use a ruler to measure the upward warping height of the four corners. Then, place the film material on the back and use a ruler to measure the downward warping height of the four corners. The upward warping height is required to be ≤20mm and the downward warping height is ≤-10mm. The results are shown in Table 2.
[0082] (3) After the coating is completed and the machine is removed, three samples are cut according to the average width of the film, and the sample specifications are 340*340mm. The samples are baked in a 150°C oven for 5 minutes. After the baking is completed, when the temperature drops below 70°C, the samples are taken out and the film surface reflection is tested with the film surface facing up. Then the film material is placed in the etching solution and etched for 10 minutes in the 400-700nm band. The film surface reflection is tested again. The results are shown in Table 3.
[0083] Table 1 ITO film square resistance test results
[0084]
[0085] Note: The unit in Table 1 is Ω.
[0086] Table 2 ITO film warpage test results
[0087]
[0088]
[0089] Note: The unit in Table 2 is mm.
[0090] Table 3 Comparison of color difference before and after ITO film etching
[0091]
[0092] Note: The unit in Table 3 is %.
[0093] Referring to Table 1 and Table 2, the square resistance and warpage of the film materials in the comparative example and the embodiment meet the requirements, indicating that selecting the same indium tin target to plate the ITO layer and selecting two different indium tin targets to plate the ITO layer have little difference in the final square resistance and warpage of the ITO film.
[0094] Referring to Table 3, the difference before and after etching of the film in the comparative example is as low as 1.73% and as high as 2.32%, both exceeding 1.0%, while the difference before and after etching of the film in the embodiment of the present invention is as low as 0.30% and as high as 0.89%, both less than 1.0%, meeting the high requirements of users.
[0095] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0096] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An ultra-low square resistance ITO film with better color difference, characterized in that: It comprises a substrate layer, on which an upper coating layer, a primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially stacked; The first ITO layer is formed by plating two indium tin mixed targets with different doping ratios, wherein the molar ratio of indium tin in one indium tin mixed target is (80-99):(1-20) based on indium tin atoms, and the molar ratio of indium tin in another indium tin mixed target is (88·95):(5·12) based on indium tin atoms; The second ITO layer is formed by plating two indium tin mixed targets with different doping ratios. The molar ratio of indium tin in one indium tin mixed target is (80-99):(1.20) based on indium tin atoms, and the molar ratio of indium tin in the other indium tin mixed target is (88-95):(5-12) based on indium tin atoms.
2. The ultra-low square resistance ITO film with better color difference according to claim 1, characterized in that: The thickness of the first ITO layer is 50-250 nm.
3. The ultra-low square resistance ITO film with better color difference according to claim 1, characterized in that: The second ITO layer has a thickness of 50-150 nm.
4. The ultra-low square resistance ITO film with better color difference according to claim 1, characterized in that: The molar ratio of silicon to aluminum in the silicon-aluminum mixed layer is (75-99): (1-25) based on silicon and aluminum atoms.
5. The ultra-low square resistance ITO film with better color difference according to claim 1, characterized in that: The thickness of the silicon-aluminum mixed layer is 1-30 nm.
6. The ultra-low square resistance ITO film with better color difference according to claim 1, characterized in that: The base layer material is selected from SiO2, Ti, TiO2, Si, Al2O3, MgF2, SiO, HfO2, SnO2 and Y2O3.
7. The ultra-low square resistance ITO film with better color difference according to claim 1, characterized in that: The thickness of the base layer is 0.2-20 nm.
8. The ultra-low square resistance ITO film with better color difference according to claim 1, characterized in that: A lower coating layer is provided on the side of the substrate layer away from the upper coating layer, and both the upper coating layer and the lower coating layer are acrylic resin layers.
9. The method for preparing an ultra-low square resistance ITO film with better color difference according to any one of claims 1 to 8, characterized in that: The steps include: Taking a substrate layer, coating an upper coating layer and a lower coating layer on both sides of the substrate layer respectively, and setting a high temperature protective film on the lower coating layer; A primer layer, a silicon-aluminum mixed layer, a first ITO layer and a second ITO layer are sequentially plated on the upper coating layer; A positive protective film is provided on the second ITO layer.
10. The ultra-low square resistance ITO film with better color difference according to claim 9, characterized in that: During plating, the vacuum degree is 1×10 -4 Pa or less, the water vapor value is 9×10 -5 Below pa, the reaction gas is a mixed gas of argon, nitrogen and oxygen, and the flow ratio of argon, nitrogen and oxygen is (60-80):(20-35):(5-10).